Effective improvement in poly(bisphenol‐A carbonate) crystallinity by ionization of its polyamide‐66 heterogeneous nucleator: The role of ion‐dipole interactions. Issue 3 (21st May 2020) - Ding, Dachuan; Luo, Jingjin; Wang, Jie; Yu, Zixin; Tian, Yuanfu; Tan, Jinqiang; Song, Zhiyuan; Tao, Qian; Hu, Tao; Wu, Chonggang
Abstract: Ionized polyamide (PA)‐66 was successfully prepared at room‐temperature using HCl (0.31 mol%) and CaCl2 (2.3 mol%), respectively. The PA‐66 ionenes, compared with the non‐ionized PA‐66, are used as a nucleator along with cholesteryl nonanoate (CN) as an active plasticizer to improve poly(bisphenol‐A carbonate) (PC) crystallization. The results show the PA‐66‐HCl heterogeneously nucleates PC more effectively than the PA‐66‐CaCl2 . The possible rationale is that the strong ion‐dipole interactions (IDIs) of the PA‐66‐HCl remarkably boost the PC/PA‐66‐HCl interfacial compatibility, which results in the formation of considerably finer and denser PA‐66‐HCl crystals with significantly enhanced nucleation efficiency. However, owing to its higher ion content, the PA‐66‐CaCl2 seems to have much stronger IDIs with PC that the resulting compatibility (i.e., thicker amorphous interlayers) dramatically inhibits PC crystallization. Abstract : Polyamide (PA)‐66 ionized using HCL and CaCl2 was prepared and used as a nucleator of poly(bisphenol A carbonate) (PC) crystallization. Due to the occurrence of the strong ion‐dipole interactions between PA‐66 and HCL, a more controlled and improved interfacial compatibility was achieved. The results show that PC treated with HCL can form denser crystals with significantly enhanced nucleation efficiency.